A magnetically-activated thermal switch without moving parts. (1st October 2019) - Rodrigues, C.; Dias, M.M.; Martins, L.; Silva, D.J.; Araújo, J.P.; Oliveira, J.C.R.E.; Pereira, A.M.; Ventura, J.
Highlights: A novel magnetic thermal switch without moving parts was designed and tested. The temperature gradient between hot and cold sides reduces significantly. The performance of the MATS depends on the initial temperature gradient and applied power. With increasing power, the efficiency of the heat exchange process increases. Abstract: With the ever increasing power dissipation in electrical devices, new thermal management solutions are in high demand to maintain an optimal operating temperature and efficient performance. In particular, recently developed magnetically-activated thermal switches (MATSs) provide an alternative to existing devices, using the magnetic and thermal properties of superparamagnetic nanofluids to dissipate heat in a controlled manner. However, the presence of moving parts is a major drawback in these systems that must still be addressed. Herein, we present a compact and automatized MATS composed by an encapsulated superparamagnetic nanofluid and an electromagnet allowing to activate the MATS without any moving part. We investigate the effect of different temperature gradients ( 10, 26 and 40 °C) and powers applied to the coil (6.5, 15, 25 and 39 W) on the performance of this novel MATS. The results show that the highest ( 44.4 % ) and fastest ( 0.6  °C/s) temperature variation occur for the highest studied temperature gradient. On the other hand, with increasing power, there is also an increase in the efficiency of the heat exchange process between the two surfaces. These results remove one of the main barriers preventing the actual application of magnetic thermal switches and opens new venues for the design of efficient thermal management devices.